Assessing the impact of country risk on Non-Bank Financial Intermediation and Traditional Banking credit in African countries: A comparative analysis - Oyetade, Damilola Tope; Aboluwodi, Damilola; Muguto, Hilary Tinotenda; Muguto, Lorraine; Muzindutsi, Paul-Francois (Jurnal Ekonomi Bisnis Manajemen Prima, 2025)
This study examines the impact of country risk on Non-Bank Financial Intermediaries (NBFIs) in Sub-Saharan Africa and their role in credit intermediation between 2000 and 2022. NBFIs, crucial to emerging economies, provide credit to individuals and businesses, especially where formal institutions fall short. Using a fixed effects model with corrected standard errors on panel data from 30 Sub-Saharan African countries, the study compares the effects of country risk on NBFIs and traditional banks. Findings show that while country risk negatively affects NBFI lending, the impact is insignificant, contrasting with its significant negative effect on traditional bank credit. Financial development has a divergent effect, boosting traditional banks credit but hindering NBFIs. Furthermore, regulatory quality positively influences credit growth in both sectors, while the banking sector enhances NBFI activities and vice versa. These findings offer valuable insights for policymakers and regulators, highlighting NBFIs’ vital role in sustaining credit flow amid rising country risk in Africa’s evolving financial landscape.